Al-Awbi'at fi al-Turats al-Islami: al-Tashkhis wa al-Waqaya wa al-'Ilaj - Hadj Benaired (Indonesian Journal of Islamic Literature and Muslim Society)
The Islamic world, like other nations, has faced numerous pandemics throughout history, profoundly shaping its societal landscape. Muslims historically addressed such challenges in accordance with the teachings of Prophet Muhammad (peace be upon him), employing both spiritual practices, such as supplication and purification rituals, as well as practical measures. Among the most devastating pandemics was the Black Plague in the mid-8th century, which ravaged the Islamic world and beyond, spanning Asia and Europe. This pandemic reshaped demographics and left a lasting impact on states and societies. Islamic scholars and physicians played pivotal roles during this crisis, documenting its effects, proposing solutions, and contributing to medical advancements. This research aims to explore the contributions of Muslim scholars and doctors in combating the Black Plague, documenting their writings, proposals, and medical interventions. By examining their efforts, we gain insights into historical approaches to pandemics and strategies for prevention and treatment.